Comparison of Pre and Post Tonsillectomy Clinical Assessment of Weight with Increase in Weight in Children - M Naeem, Waqas Javaid, Raana A. Akbar, Hira Andleeb, Syed T. Bukhari, Sultan B. Munir, Maryam Fatima, Mirza M. Sarwar, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Tonsils and adenoid are part of local immunity near the entrance of respiratory and digestive tracts. However they may become infected and can be a source of chronic or recurrent infections and can lead to OSAS if enlarged. In case of significant morbidity surgical resection is indicated. Aim: To study the relationship between tonsillectomy and increase in weight in children. Setting: ENT Unit II of Fatima Jinnah Medical University and Sir Ganga Ram Hospital Lahore Duration: 1st February 2021 to 31st January 2022. Study design: Quasi experimental study Method: All patients of 5 to 9 years of age with history of recurrent tonsillitis and obstructive sleep apnea syndrome were included. Total of 88 patients selected with non probability convenient sampling. Clinical assessment was done for recurrent and chronic tonsillitis and tonsil hypertrophy causing OSAS. Pre operative weight measured and compared with post operative weight at 3 months follow up. Results: Out of 88 participants 74(84.1%) have recurrent tonsillitis and 75(85.2%) have OSAS. Mean pre operative weight was 16.6591 kg and mean post operative weight was 19.8182 kg. Paired sample t test was applied and p value was calculated which was statistically significant. Conclusion: There is a significant increase in weight after tonsillectomy in children at 3 months follow up that is beneficial in terms of quality of life, school performances, behavior and mental well being.